Big Data : Principles and Practice - Wright, Ethan (United States : Willford Press, 2021)
Big data is a field that deals with the ways to analyze, systematically extract information from, or otherwise deal with data sets that are too large or complex to be dealt with by traditional data-processing application software. Data with many columns offer greater statistical power, while data with higher complexity may lead to a higher false discovery rate challenges associated with. Big data analysis comprise capturing data, data storage, data analysis, sharing, transfer, visualization, querying, updating, information privacy, and data source. Big data is associated with three key concepts of volume, variety, and velocity. Big data has applications for government, international development, healthcare, education, insurance, media, the internet of things, and IT. This book outlines the principles and applications of big data in detail. It discusses the fundamentals as well as modern approaches of this field. As big data is emerging at a rapid pace, the contents of this book will help the readers understand the modern concepts and applications of the subject
Includes index.
Includes bibliographical references.
Keywords: Management information systems; Computer science; Database management; Data structures (Computer science).; Software engineering